Kajian Determinisme Lingkungan terhadap Budaya Pangan di Indonesia - Hidayat, Manarul; Kurnia Priambodo, Tio (Jurnal Ekologi, Masyarakat dan Sains, 2023)
Indonesian people's food has socio-cultural aspects that manifest in food culture. Through a literature review it is known that there is an influence of the natural environment (environmental determinism) on the food culture of the Indonesian people, including food ingredients, food processing, food consumption, to the triad of food. In West Indonesia, Central Indonesia, and East Indonesia, there is the triad of food or a tendency for the same trinity of food ingredients, namely 1) fish which represents meat, 2) coconut which appears in coconut milk oil emulsion, and 3) chili which is presented in chili shape. The tropical and hot equatorial natural environment encourages the use of these three ingredients, both to support the preservation of food and to support the body's resistance.